KNOWLEDGE AND SELFCARE PRACTICES AMONG DIABETICS - S, Sheeba; Ak, Sneha; Biju, Veena (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objectives of the study were to assess the knowledge and self-care practices among patients with type 2 diabetes mellitus. Methods: Quantitative approach with descriptive survey design and convenience sampling technique was used. The study was conducted among 100 patients with type 2 diabetes mellitus, from the Inpatient and Outpatient Department of Amrita Institute of Medical Science, Kochi. A structured knowledge questionnaire and structured practice assessment questionnaire were used to assess the knowledge and self-care practices of the subjects. Result: Result shows that 77% subjects had good knowledge regarding diabetes and majorityof the subjects had good level of self-care practices. 63% of subjects regularly monitoring blood glucose level, 72% following proper diet, 88% of subjects taking regular medication, 84% of subjects follow proper eye care, 79% of subjects follow proper foot care, 57% of subjects maintaining ideal body weight, and only 46% of subjects doing regular exercise. There was a positive relationship (r=0.09) between level of knowledge and self-care practice of the subjects and no significant association between knowledge level and selected sociodemographic variables. Conclusion: It is important that the patient should have adequate knowledge regarding diabetes and they should follow proper self-care practices to prevent further complications.